Husband's role in the birth preparedness and complication readiness program in the Kebumen District, 2022 - Silayuningsih, Devvy Herawati; Wiratama, Bayu Satria; Wahab, Abdul (BKM Public Health and Community Medicine, 2024)
Purpose: The involvement of the husband during pregnancy helps a mother to make timely decisions to avoid delays. Identifying the level of husband involvement in birth preparedness and complication readiness (BPCR) is crucial, as the husband is the primary decision-maker in household and health service-related matters. The purpose of this study is to analyze the role of husbands in BPCR in Kebumen District in 2022. Method: This research was a cross-sectional study design. Primary data was collected using questionnaires for 300 respondents, including pregnant women in the third trimester and their husbands, through cluster random sampling. The dependent variable was the role of husbands in BPCR; the independent variables were the wife's reproductive status, the husband's socioeconomic status, the husband's knowledge about pregnancy, labor, and postpartum complications, and the husband's knowledge about BPCR. The data was analyzed using univariate, bivariate analysis with binomial regression, and multivariate analysis with Poisson regression modification. Results: The proportion of husbands’ roles in BPCR was 71.33%. Multivariate analysis indicates that husbands employed in the government or private sector are 36% (aPR 1.36; 95% CI 1.10-1.68) and 14% (aPR 1.14; 95% CI 1.02-1.28) more likely to play a supportive role in BPCR, respectively. Husbands with good knowledge about the danger signs during pregnancy, labour, and postpartum (aPR 1.23; 95% CI 1.02-1.50) and those knowledgeable about BPCR (aPR 9.83; 95% CI 4.83-19.96) have a significant positive impact on their role in BPCR. Conclusions: Husbands’ participation in birth preparedness and complication readiness was found to be quite good. We recommend that improving the educational level is important to increase husbands’ involvement in the birth preparedness and complication readiness plan.